The role of airway endoscopy in children. Issue 4 (April 2015) - Wilkinson, Sophie; Sudarshan, Purushothaman; Smyth, Alan R.; Daniel, Matija
Abstract: Airway endoscopy is an essential tool in the investigation and management of paediatric airway and respiratory pathology. Examination can be performed using a variety of rigid and/or flexible endoscopes, each with specific advantages and limitations. Awake fibreoptic examination of the airway enables timely and dynamic respiratory tract examination, but is limited to visualisation of more proximal anatomy, from pharynx to glottis. This technique is predominantly used for diagnostic purposes and has minimal therapeutic capabilities. Conversely, endoscopic techniques used in distal airway examination facilitate simultaneous interventional techniques, but necessitate general anaesthesia. Laryngotracheobronchoscopy using rigid instruments examines the airway to main bronchi and has multiple therapeutic applications. Flexible bronchoscopy allows examination of the respiratory tract beyond main bronchi. These techniques are complementary, and close collaboration between the different specialties involved is essential.